Pengembangan LKPD Berbasis Science, Technology, Engineering, Arts And Mathematics (STEAM) Kelas VI Dalam Mata Pelajaran Ilmu Pengetahuan Alam (IPA) - Ardian Nopiansyah Nopiansyah; Endang Widi Winarni; Irwan Koto (UNIB Press, 2022)
This study aims to develop a STEAM-based LKPD. The type of research used is research and development (Research & Development) by modifying the Sugiyono model adopting 6 steps, namely potential problems, gathering planning information, product design, design validation, product revision, product testing. The research data were obtained through questionnaires, interview guidelines, validation sheets, and student response questionnaires. Aspects that are validated include the feasibility of the material, language, presentation and graphics. There are 6 validators (raters) involved in validating consisting of experts and practitioners. Data on student responses to LKPD were obtained from the responses of 15 grade VI students at SDN 9 Pendopo. Based on the results of research and development, it was concluded that the STEAM-based LKPD was very suitable for use in learning science content for class VI SDN 9 Pendopo students.